Mating orientation and dark triad personality on sexting behavior: A comparative study between male and female emerging adults in Malaysia - Lee, Yih Wen (2024)
Sexting behaviour among emerging adults is a prevalent phenomenon with implications for sexual health and interpersonal relationships. This cross-sectional study investigated the relationship between mating orientations (short-term mating orientation, long-term mating orientation and sociosexual behaviour), dark triad personality traits (narcissism, Machiavellianism, and psychopathy), and sexting behaviour with gender as a moderator among emerging adults in Malaysia. Utilizing self-report measures, including the Sexting Behaviour Scale, the Dirty Dozen Dark Triad questionnaire, and the Multidimensional Sociosexual Orientation Inventory, participants (n = 183) provided insights into their sexting behaviour. Results indicated no indication of addiction-level sexting behaviour among the sample. Significant associations were found between mating orientations and sexting behaviour, with long-term mating orientation showing a negative correlation, suggesting conflicting values between sexting and relationship ideals. Psychopathy emerged as a significant predictor of sexting behaviour, indicative of impulsive tendencies among participants engaging in sexting. Surprisingly, narcissism and Machiavellianism did not correlate significantly with sexting behaviour, possibly due to concerns about social consequences and reputational damage. Moreover, gender did not moderate the relationships between any of the mating orientations, dark triad personality traits, and sexting behaviour, suggesting a universal association across genders. These findings offer valuable insights into the unique associations between mating orientations, dark triad personality traits and sexting behaviour across female and male emerging adults in Malaysia, informing the development of targeted interventions and educational initiatives to promote responsible digital communication practices.